Bacterial co-fermentation mediated synthesis of chitosan from Procambarus clarkii enhances disease resistance in rice - Lirong Wei; Yiqiong Sun; Yingqiao Wan; Shangyu Gao; Sun Tae Kim; Ravi Gupta; Yiming Wang (Carbohydrate Polymer Technologies and Applications)
The increasing dietary demand for red swamp crayfish (Procambarus clarkii) in China has resulted in a significant rise in the quantity of its by-products, which are currently underutilized or discarded. Chitosan, a widely used plant immune inducer, is one of the major components found in red swamp crayfish shells (RSCS). However, the utilization of chitosan derived from RSCS in agriculture is hindered by the lack of an efficient microbial fermentation-based production system. To address this issue, this study aims to establish a chitosan fermentation procedure by using RSCS as substrate. The efficiency by using Bacillus followed with Acetobacter for a continuous co-fermentation tested. Bacillus NJ-B2 or NJ-B3 with Acetobacter NJ-A1 demonstrated the highest co-fermentation efficacy, achieving 95 % deproteinization and 90 % demineralization of RSCS, respectively. The extracted chitosan was characterized by fourier transform infrared and scanning electron microscopy. Notably, the application of this RSCS-derived chitosan significantly improves rice resistance against Xanthomonas oryzae pv. oryzae, Magnaporthe oryzae, and Ustilaginoidea virens. These findings collectively indicate that this established method can effectively produce chitosan from RSCS via microbial fermentation, providing an environmentally friendly way for plant protection.